2015
DOI: 10.1080/09064710.2014.956789
|View full text |Cite
|
Sign up to set email alerts
|

Use of long-term monitoring data to derive a relationship between nitrogen surplus and nitrate leaching for grassland and arable land on well-drained sandy soils in the Netherlands

Abstract: The decrease in nitrogen (N) use in agriculture led to improvement of upper groundwater quality in the Sand region of the Netherlands in the 1991-2009 period. However, still half of the farms exceeded the European nitrate standard for groundwater of 50 mg/l in the 2008-2011 period. To assure that farms will comply with the quality standard, an empirical model is used to derive environmentally sound N use standards for sandy soils for different crops and soil drainage conditions. Key parameters in this model ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
(42 reference statements)
1
20
0
8
Order By: Relevance
“…In order to ensure that the nitrate concentrations in oxidized aquifers will not exceed 50 mg/L and to conserve the natural denitrification capacity of reduced aquifers, the German Working Group on water issues of the Federal States and the Federal Government (LAWA) requires that the nitrate concentration in the leachate should not exceed 50 mg NO 3 /L [28]. Similar considerations are reflected in the groundwater strategies of other countries [29,30]. Against this background, the nitrate concentration in the leachate can be considered as the decisive starting-point to determine the N reduction required [31].…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure that the nitrate concentrations in oxidized aquifers will not exceed 50 mg/L and to conserve the natural denitrification capacity of reduced aquifers, the German Working Group on water issues of the Federal States and the Federal Government (LAWA) requires that the nitrate concentration in the leachate should not exceed 50 mg NO 3 /L [28]. Similar considerations are reflected in the groundwater strategies of other countries [29,30]. Against this background, the nitrate concentration in the leachate can be considered as the decisive starting-point to determine the N reduction required [31].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, ADF empowers farmers to proactively address environmental issues and the paper discusses the development, guidance, principals and goals of ADF and contrasts this with other farm monitoring projects, where the sources of nutrient impairment are the subject of ongoing mitigation. Fraters et al (2015) address how to use long-term monitoring data to develop a method for calculating the nitrate nitrogen leaching fractions (NLFs) by using data from a random sample of commercial arable farms and dairy farms that were monitored during the period 1991-2009. The results showed that N surplus leached almost completely from the root zone of arable land on the most vulnerable soils, i.e., deep, well-drained sandy soils (95%) confidence interval of NLF (0.80-0.99), while for grassland only half of the N surplus leached from the root zone of grassland (0.39-0.49).…”
Section: Uncertainty and Modellingmentioning
confidence: 99%
“…According to Kupiec (2015), reference levels of N-surplus defining the risk of water hazards are quoted in various sources. Research results indicate that N-surplus can be a good predictor of groundwater nitrate pollution (Wick et al, 2012;Fraters et al, 2015;Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%